Aqua regia extractable selenium concentrations of some Scottish topsoils measured by ICP-MS and the relationship with mineral and organic soil components - Shand, Charles A; Balsam, Matthias; Hillier, Stephen J; Hudson, Gordon; Newman, Gareth; Arthur, John R; Nicol, Fergus (Journal of the science of food and agriculture, 2010)
BACKGROUND: To provide information concerning the geographical distribution of selenium (Se) in the soils of Scotland, we analysed 47 arable soils selected on the basis of their parent rock, which were expected to have relatively high, low or unclassified Se concentrations. To investigate relationships between the actual minerals in the soils and the aqua regia extractable Se concentration of the soil, soil minerals were quantified by X-ray diffraction.RESULTS: The aqua regia extractable Se concentrations of the soils were between 0.19 and 1.46 mg kg⁻¹. No simple correlation between the aqua regia extractable Se concentrations of the soil and the parent rock classification estimated by soil survey was evident. Partial least squares analysis revealed that the aqua regia extractable Se concentration of the soils was positively related to loss on ignition (LOI) or C concentration and negatively related to the K-feldspar concentration, with other minerals being less important.CONCLUSION: The Se concentration of arable topsoils from Scotland is more related to LOI or carbon concentration, with parent material being less important.